Analysis of GSI Herbal Medicine Product Sales Strategy Using SWOT Matrix and QSPM Methods - Muhammad Nabil Daris Taufail; Deny Andesta (Universitas Islam Raden Rahmat, Malang, 2026)
In its efforts, Jamu GSI HERBAL products are only marketed to the surrounding community and are unable to compete with health products that offer instant solutions. Therefore, data was collected through observation, in-depth interviews, and questionnaires with four employees and four consumers, as well as strategy validation by the owner and experts at the Mustofa Clinic. The SWOT analysis identified 5 strengths, 3 weaknesses, 3 opportunities, and 3 threats. The results of the IFE (3.86) and EFE (3.67) matrices placed the company in the Grow and Build position. The QSPM analysis set the main priority on ST 1 (score 6.76): increasing hygienic production through a partnership with the Health Office and diversifying variants (syrup/candy). This research emphasizes that legal standardization (BPOM, BPJPH, HKI) is key to transforming MSMEs toward modern markets. This strategy implies increased consumer confidence and production efficiency. Further research recommendations include analyzing the financial impact of transitioning from manual tools to automated machines on profit margins. With the implementation of this strategy, GSI HERBAL is expected to compete competitively and sustainably.